MENANAMKAN JIWA WIRAUSAHA MELALUI KERAJINAN KAIN TENUN TRADISIONAL DI DESA PAJAM KECAMATAN KALEDUPA SELATAN KABUPATEN WAKATOBI - Sarleni, Sarleni; Jeti, La; Marwah, Marwah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to instill an entrepreneurial spirit in six-year-old children through traditional woven fabric crafts in Pajam Village, South Kaledupa District, Wakatobi Regency. A participatory qualitative approach was employed, involving children, teachers, parents, and local artisans. Activities such as making brooches, bracelets, keychains, and wallets from traditional woven fabric were designed to foster entrepreneurial values, including self-confidence, responsibility, leadership, originality, and goal orientation. Observations and interviews revealed that children developed entrepreneurial skills through these creative processes. The support of parents and teachers played a vital role in enhancing children's interest and enthusiasm. The study concludes that traditional woven fabric crafts are an effective learning medium for nurturing an entrepreneurial mindset from an early age while simultaneously preserving local cultural heritage.